Cover Feature: Selective Transformation of Well‐Defined Alkenyllithiums to Alkenylmagnesiums via Transmetalation (Chem. Eur. J. 13/2018). Issue 13 (16th January 2018) - Zhu, Miaomiao; Liu, Liang; Zhang, Yongliang; Yu, Hai‐Tao; Zhang, Wen‐Xiong; Xi, Zhenfeng
Abstract : Selective transformation of alkenyllithiums to alkenylmagnesiums via simple transmetalation has been achieved. The synthesis, structure, and mutual transformation of three different organomagnesiums by adding Grignard reagent and/or MgCl2 to dilithio reagents are described. These magical transformations triggered by Grignard reagent and/or MgCl2 are similar to the traditional Face‐changing art originating from the Sichuan province of China. More information can be found in the Full Paper by W.‐X. Zhang, Z. Xi et al. onpage 3186 .